EVALUASI KELAYAKAN USAHA SARANG BURUNG WALET DI KECAMATAN TELAGA ANTANG KABUPATEN KOTAWARINGIN TIMUR - Danny Sumardi; Pordamantra, Pordamantra; Sunariyo, Sunariyo (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2018)
This study aims to evaluate the feasibility of swallow nest business in terms of financial aspects. Financial aspects ware analyzed using the methods of Net Present Value, Net B / C Ratio, Internal Rate of Return, Payback Period, and Sensitivity Analysis. This research is quantitative research. The subject of this research was the swallow nest business of Mr. Suwaji and the object of his research was the feasibility of a swallow nest business. Methods of collecting data using interview techniques and documentation. The data analysis technique of this research is quantitative analysis to assess financial aspects. Based on the results of the study showed that in terms of the financial aspects, the swallow nest business of Mr. Suwajiwas feasible to run because the value of NPV > 0, Rp 334.415.629; Net B/C > 1 which is 2,19; IRR > i, which is 35,18%; Payback Period is 4,4 years (4 years 4 month). These values are in accordance with the investment assessment criteria, so that Mr. Suwaji's swallow nest business is feasible to carry out and continue. Sensitivity analysis in swallow nest business shows that this businessis sensitive to production changes, namely (a decrease in production by 30% and a decrease in selling price by 20%) because it has a significant decrease in the value of NPV, IRR, and Net B / C. But the business is still feasible to run.